2017
DOI: 10.1007/s00383-017-4222-0
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey of incidence rates and risk factors of inguinal hernia in preterm children

Abstract: Birth weight under 2500 g is a significant risk factor for IH repairs. Other risk factors are male gender, past history of lung diseases, and ventilator supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Thus, they recommended herniorrhaphy during NICU admission, especially in VLBW infants, who have a high risk of incarceration while waiting for operation. By contrast, the incidence of incarceration was not different between preterm and term infants, and was low in both groups according to a nationwide survey in Taiwan (0.43% in preterm infants vs. 0.41 % in term infants, P=0.959) 20) . Relatively few incarcerations were reported in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, they recommended herniorrhaphy during NICU admission, especially in VLBW infants, who have a high risk of incarceration while waiting for operation. By contrast, the incidence of incarceration was not different between preterm and term infants, and was low in both groups according to a nationwide survey in Taiwan (0.43% in preterm infants vs. 0.41 % in term infants, P=0.959) 20) . Relatively few incarcerations were reported in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…In a study of 79,794 children, the rate of incarceration decreased as age increased (20). While some studies have reported a positive or negative association between prematurity and incarceration, two studies found no relationship (8,20,22,23).…”
Section: Discussionmentioning
confidence: 87%
“…Because obliteration of the processus vaginalis begins during gestation, canal of Nuck and other inguinal hernias are associated with prematurity and may occur in 9%–11% of infants born prematurely (7). A study of 92,308 children found that inguinal hernias may be associated with lung disease and mechanical ventilation, which may be explained by the increase in intraabdominal pressure present in these situations (8).…”
Section: Discussionmentioning
confidence: 99%
“… 6 Other risk factors include lung disease and mechanical ventilation, where herniation is related to increased intra-abdominal pressure. 7 …”
Section: Discussionmentioning
confidence: 99%